Sketchbook for the artist - Simblet, Sarah (New York, N.Y. : DK Pub., 2009)
An introduction to the art of drawing explores a wide variety of media and techniques for both novice and experienced artists, with practical guidelines on such topics as shape, shading, portraiture, architectural renderings, nature, and perspective.
Animals -- Plants and gardens -- Architecture -- Objects and instruments -- The body -- Portraiture -- Costume -- Gatherings -- Earth and the elements -- Abstract lines -- Gods and monsters.
Includes index.
Keywords: Drawing -- Technique